2016
DOI: 10.1371/journal.pone.0149731
|View full text |Cite
|
Sign up to set email alerts
|

Triglyceride Glucose-Body Mass Index Is a Simple and Clinically Useful Surrogate Marker for Insulin Resistance in Nondiabetic Individuals

Abstract: BackgroundInsulin resistance (IR) and the consequences of compensatory hyperinsulinemia are pathogenic factors for a set of metabolic abnormalities, which contribute to the development of diabetes mellitus and cardiovascular diseases. We compared traditional lipid levels and ratios and combined them with fasting plasma glucose (FPG) levels or adiposity status for determining their efficiency as independent risk factors for IR.MethodsWe enrolled 511 Taiwanese individuals for the analysis. The clinical usefulnes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

6
278
3
2

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 269 publications
(319 citation statements)
references
References 38 publications
(52 reference statements)
6
278
3
2
Order By: Relevance
“…Considering that insulin levels are not usually achieved during general health check-up in South Korea, calculating the HOMA-IR to estimate IR is somewhat inconvenient for this population. A number of previous studies identified that the TyG index is closely correlated with the HOMA-IR [9,30]. Moreover, recent data reported that the value of the TyG index predicting IR was better than that of the HOMA-IR [8,31].…”
Section: Discussionmentioning
confidence: 97%
“…Considering that insulin levels are not usually achieved during general health check-up in South Korea, calculating the HOMA-IR to estimate IR is somewhat inconvenient for this population. A number of previous studies identified that the TyG index is closely correlated with the HOMA-IR [9,30]. Moreover, recent data reported that the value of the TyG index predicting IR was better than that of the HOMA-IR [8,31].…”
Section: Discussionmentioning
confidence: 97%
“…This is also in favor of the results of our study. 20 Er et al (2016) found triglyceride-glucose index is simple and clinically useful surrogate marker for insulin resistance in non diabetic individuals. 21 The prevalence of metabolic obesity in total study …”
Section: Discussionmentioning
confidence: 99%
“…In developing countries with economic difficulties in health systems, such as Venezuela, routine measurements of plasma insulin are not easily accessible, which forces the use of other indices based on the role of glucolipotoxicity as a key element in the development of IR 29 . In this way, the TGI has recently been proposed and validated as a useful alternative in clinical settings, and has been well accepted due to the high predictive power observed with respect to other indices 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have shown that the TGI better predicts HOMA-IR levels than variables, such as the TAG/HDL index, visceral adiposity index, leptin, Apo-B/Apo-AI, and lipid parameters 29, 30 , representing a very good correspondence with this index 31 , which constitutes an important tool with high validity for the clinician when facing limited access to lab work-ups. However, in view of the wide variability of TAG levels according to the ethnic, sociocultural and genetic characteristics of each population, the need arises to evaluate their epidemiological behavior and establish reference values specific to each region.…”
Section: Discussionmentioning
confidence: 99%